Penerapan Sistem Pendukung Keputusan Dengan Metode SAW, WP, Dan Topsis Untuk Pemilihan Vendor Terbaik - Kurnia Solihin, Agung; Setiawan, Indra; Falah, Miftahul; Shadam, Muhammad; Umam, Syahrul; Rosyani, Perani (CV. Shofanah Media Berkah, 2025)
In the business and industrial world, vendor selection is very important because it has a direct impact on the success and efficiency of a company's operations. However, subjective factors and the lack of a systematic approach often affect this process. The purpose of this study is to develop and compare Decision Support Systems (DSS) using three Multi-Criteria Decision Making (MCDM) methods: Simple Additive Weighting (SAW), Weighted Product (WP), and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). Data collected from five vendor evaluation criteria are price, product quality, delivery distance, after-sales service, and after-sales service. The results of data processing show that each method produces different vendor rankings, but the SAW method produces the most consistent and easy-to-understand results.